MiR-130c-5p targets the SHVV n gene and upregulates immune cytokines (IL-6, IL-22, IL-1β) to inhibit viral replication - Wei, Jin; Ji, Yan; Bai, Yaqian; Cheng, Rui; Zhang, Jiaqi; Hu, Xianqin; Zhang, Chi (Frontiers in Immunology, 2024)
Snakehead vesiculovirus (SHVV) has led to huge economic losses in snakehead aquaculture, and its pathogenic mechanisms is still not fully understood. MicroRNAs (miRNAs), as an important class of non-coding RNAs, play a key regulatory role in the process of viral infection. In this study, SHVV infection significantly upregulated the expression of miR-130c-5p in channel catfish ovary (CCO) cells in a time-and dose-dependent manner. The further research revealed that miR-130c-5p mimic significantly inhibited, while its inhibitors promoted SHVV replication. In addition, miR-130c-5p could directly target the viral mRNA of n gene, and overexpression of miR-130c-5p could significantly decrease, and conversely, downregulation of miR-130c-5p could increase the mRNA and protein expression of the viral n gene. Meanwhile, overexpression of miR-130c-5p also upregulated the expression of immune-related genes, such as nucleotide-oligomerization domain (NOD)-like receptor subfamily C3 (NLRC3), myeloid differentiation factor 88 (MyD88), nuclear factor kappa-B (NF-κB), interleukin-6 (IL-6), interleukin-22 (IL-22), and interleukin-1beta (IL-1β) in host cells. Taken together, these results suggest that miR-130c-5p was upregulated in the host during SHVV infection, and the upregulated miR-130c-5p directly inhibited viral replication by targeting the n gene of SHVV and promoting viral nucleoprotein degradation. The up-regulated miR-130c-5p also activated the expression of immune-related genes such as NLRC3, MyD88, NF-κB, IL-6, IL-22, and IL-1β, which were involved in the regulation of the signaling pathways including NF-κB, MyD88, Toll-like receptor (TLR), NLR, and janus tyrosine kinase-signal converter and activator of transcription (JAK-STAT), to enhance the host's antiviral immune response, and thus indirectly inhibited the viral proliferation. This study contributes to a better understanding of the molecular mechanism of SHVV pathogenesis and provides a theoretical basis for the development of miRNA-based antiviral therapeutic strategies as well as potential antiviral strategies against SHVV infection.